Gramicidin inhibits cholangiocarcinoma cell growth by suppressing EGR4 - Xiaoli Gong; Liming Zou; Miaomiao Wang; Yingheng Zhang; Shuxian Peng; Mingtian Zhong; Jiankui Zhou; Xun Li; Xiaodong Ma (Artificial Cells, Nanomedicine, and Biotechnology)
Gramicidin is a well-known antibiotic and recently was reported to induced tumour cell death, however, little is understood about the molecular mechanism of gramicidin as a therapeutic agent for solid tumours. Here, we investigated the role of gramicidin in cholangiocarcinoma cells. We found that gramicidin A inhibits cholangiocarcinoma cell growth and induced the necrotic cell death. We used next generation sequencing to analyse gene expression profiles of cholangiocarcinoma cells treated with gramicidin. We identified 265 differentially expressed genes in cholangiocarcinoma cells between PBS treatment and gramicidin treatment. EGR4 was confirmed to be a target of gramicidin-induced cell growth inhibition. Furthermore, we demonstrated that downregulation of EGR4 in cholangiocarcinoma cells leads to restraining tumour cell growth. Of note, EGR4 was expressed at highest levels in cholangiocarcinoma tissues among 17 types of human cancers, and EGR4 expression positively correlated with several growth factors associated with cholangiocarcinoma. Our findings ascertain that EGR4 is a potential target in cholangiocarcinoma and suppressing EGR4 by gramicidin establish an essential mechanism for bile duct carcinoma progression.